Pre-surgery age-adjusted Charlson Comorbidity Index is associated with worse outcomes in acute cholecystitis. Issue 6 (June 2019) - Bonaventura, Aldo; Leale, Irene; Carbone, Federico; Liberale, Luca; Dallegri, Franco; Montecucco, Fabrizio; Borgonovo, Giacomo
Abstract: Background: Beneficial effects of cholecystectomy in acute cholecystitis (AC) might be weakened by complications. The age-adjusted Charlson Comorbidity Index (CCI) assesses disease relevance in the prediction of one-year mortality. Aims: To evaluate whether age-adjusted CCI predicted complications (including surgical complications, intensive care unit [ICU] admission, and in-hospital death) among patients undergoing cholecystectomy for AC. Associations between age-adjusted CCI and the length of hospital stay have been also evaluated. Methods: 271 patients were enrolled at Ospedale Policlinico San Martino (Genoa, Italy) between 2005 and 2013. Clinical data and blood samples were collected. Results: Patients' median age was 67 years. They underwent more frequently video-laparoscopic cholecystectomy with a limited rate of conversion to open cholecystectomy. Surgical complications occurred in 23 patients (8.5%). 6 patients (2.2%) needed ICU admission, while death occurred in 4 patients (1.5%). According to the cut-off point identified by ROC curve, an age-adjusted CCI cut-off value of 5 was found predictive for in-hospital complications also when confounders were considered (OR 1.35, 95% CI 1.02–1.79, p  = 0.035). No association between adjusted CCI and the length of hospital stay was found. Conclusions: In patients surgically treated for AC, age-adjusted CCI could represent an additional tool, along with available risk scores, to help surgeons in choosing the best therapeutic option.